Laughing and Learning: Exploring the Impact of Humour in Enhancing Biology Learning Outcomes - ONOWUGBEDA, Franklin Ufoma; AJOSE, Okunola Oluwagbotemi; IGE, Adeleke Michael; ODEKEYE, Ola Tokunbo; FASINRO, Kabiru Sasaenia; AGBANIMU, Deborah Oluwatosin (Ilorin Journal of Education, 2024)
Biology, with its terminology, complex processes and extensive memorisation requirements poses a hurdle for many students which necessitate a more comprehensive and interactive learning approach. The objective of this study was to examine the potency of humour-based teaching approach to enhance the performance of secondary school students in biology. The study was a quasi-experimental design of a non-equivalent pretest-posttest control group design. The sample comprised 104 SS2 students from the intact classes of two purposively selected schools in Lagos State. These schools were randomly assigned as experimental and control groups. Achievement data were collected through a micro-organism achievement test (MAT) with a reliability value of 0.76. For four weeks, students in the experimental group received instruction on micro-organisms with the incorporation of general and content-specific humour while students in the control group received the same learning experience without elements of general and specific humour. Since one dependent variable (achievement) was of interest in this study, the data collected were analysed using ANCOVA. Results from the analysis of covariance showed a statistically significant difference in the achievement of students F (1, 101) = 304.71; p < .05. This implied that the technique was potent in enhancing the performance of students. Thus, this study recommends the incorporation of a variety of humour that will appeal to different age group and cultural background of students, ensure that the humour is relevant to the biology content being taught, and foster a positive and inclusive classroom environment.